Domains of physical activity and risk behaviours in adolescents in Northeast Brazil: a monitoring study 2011 and 2016 (Research, Society and Development, 2021)
The study aims to analyze the prevalence and the association of the domains of Physical Activity in leisure, at school and in commuting with risk behavior indicators in schoolchildren from the state of Sergipe, Brazil, 2011-2016. The study is about two epidemiological surveys with a cross-sectional design carried out in 2011 and 2016, with a representative sample of students from the State Education Network of Sergipe, composed of 8143 adolescents (2011 = 3992; 2016 = 4151), aged between 14 and 19 years old. The instrument used was the Global School-based Student Health Survey (GSHS). The data were analyzed using descriptive statistics, application of the chi-square test for inferential analysis and crude and adjusted binary logistic regression for association between variables. The results showed that NIAF in Leisure was associated with exposure to sedentary behavior in the two surveys (2011: OR = 1.78; 95% CI 1.56-2.03 / 2016: OR = 2.14; 95% CI 1.88-2.44), with the fact of not smoking tobacco in 2011 (OR = 2.11; 95% CI 1.61-2.79), and with non-drug users (OR = 1.65 ; 95% CI 1.19-2.32) and that consumed low portions of fruit in 2016 (OR = 1.32; 95% CI 1.09-1.62). School NIAF was associated with low fruit consumption (2011: OR = 2.14; 95% CI 1.51-3.05 / 2016: OR = 2.61; 95% CI 1.96-3.50). It is concluded that there was a high prevalence of NIAF among the surveys and the Physical Activity domains are differently associated with behavioral aspects according to the exposure of young people to risk factors.